The Absence of Legal Consequences for Ignoring the Obligation to Submit SPDP to the Reporter and the Reported Party: A Review of the Implementation of Constitutional Court Decision Number 130/PUU-XIII/2015 - Yedi Kusnadi; Arya Ramadhan Tangdilintin; Ahmad Syahird (IHSA Institute, 2025)
This study aims to examine in depth the legal aspects of the neglect of the obligation to submit SPDP to the reporter and the reported party after the Constitutional Court Decision No. 130/PUU-XIII/2015. This research is of a normative legal nature, with data collection techniques conducted through library research, namely laws and regulations, case studies, namely Constitutional Court decisions, and conceptual approaches. Additionally, the author also conducted library research using data and books related to the research topic. The data obtained were analyzed qualitatively and then presented descriptively. The research results indicate that: 1) Constitutional Court Decision No. 130/PUU-XIII/2015 explicitly expands the obligation of investigators to submit the SPDP not only to the public prosecutor but also to the reported party and the complainant/victim within a maximum period of 7 (seven) days from the issuance of the investigation order. This reflects the principle of due process of law and guarantees constitutional rights as enshrined in Article 28D(1) of the 1945 Constitution. Although this provision is self-executing in nature and has been adopted in Regulation of the Chief of the Indonesian National Police No. 6 of 2019, significant disparities still exist in its implementation; and 2) The absence of clear legal consequences for violations renders this norm ineffective, as stated by Hans Kelsen. The SPDP plays a crucial role in ensuring human rights and legal protection for all parties involved in the criminal justice process